YAP1 Withdrawal in Hepatoblastoma Drives Therapeutic Differentiation of Tumor Cells to Functional Hepatocyte‐Like Cells. Issue 3 (8th February 2021) - Smith, Jordan L.; Rodríguez, Tomás C.; Mou, Haiwei; Kwan, Suet‐Yan; Pratt, Henry; Zhang, Xiao‐Ou; Cao, Yueying; Liang, Shunqing; Ozata, Deniz M.; Yu, Tianxiong; Yin, Qiangzong; Hazeltine, Max; et al.
Abstract : Background and Aims: Despite surgical and chemotherapeutic advances, the 5‐year survival rate for stage IV hepatoblastoma (HB), the predominant pediatric liver tumor, remains at 27%. Yes‐associated protein 1 (YAP1) and β‐catenin co‐activation occurs in 80% of children's HB; however, a lack of conditional genetic models precludes tumor maintenance exploration. Thus, the need for a targeted therapy remains unmet. Given the predominance of YAP1 and β‐catenin activation in HB, we sought to evaluate YAP1 as a therapeutic target in HB. Approach and Results: We engineered the conditional HB murine model using hydrodynamic injection to deliver transposon plasmids encoding inducible YAP1 S127A, constitutive β‐catenin DelN90, and a luciferase reporter to murine liver. Tumor regression was evaluated using bioluminescent imaging, tumor landscape characterized using RNA and ATAC sequencing, and DNA footprinting. Here we show that YAP1 S127A withdrawal mediates more than 90% tumor regression with survival for 230+ days in mice. YAP1 S127A withdrawal promotes apoptosis in a subset of tumor cells, and in remaining cells induces a cell fate switch that drives therapeutic differentiation of HB tumors into Ki‐67‐negative hepatocyte‐like HB cells ("HbHeps") with hepatocyte‐like morphology and mature hepatocyte gene expression. YAP1 S127A withdrawal drives the formation of hbHeps by modulating liver differentiation transcription factor occupancy. Indeed, tumor‐derived hbHeps, consistent with their reprogrammed transcriptional landscape, regain partial hepatocyte function and rescue liver damage in mice. Conclusions: YAP1 S127A withdrawal, without silencing oncogenic β‐catenin, significantly regresses hepatoblastoma, providing in vivo data to support YAP1 as a therapeutic target for HB. YAP1 S127A withdrawal alone sufficiently drives long‐term regression in HB, as it promotes cell death in a subset of tumor cells and modulates transcription factor occupancy to reverse the fate of residual tumor cells to mimic functional hepatocytes.